Role of Salivary Chemerin in Oral squamous cell carcinoma (OSCC) Patients with and without Chronic Periodontitis - Sidrah Mahmood Mughal; Mervyn Hosein; Sana Mirza; Moazzam Ali Shahid; Aiza Suhail Khan (ziauddin University, 2024)
Background: Chemerin is a multifunctional protein that plays a role in immunological function, chemotaxis, energy metabolism, and basic cell activities. Chemerin dysregulation contributes significantly to tumor angiogenesis and disease progression. The study aimed to assess salivary chemerin levels in Oral squamous cell carcinoma (OSCC) patients with/without chronic periodontitis, as well as, investigate the relationship between chemerin levels and OSCC stages. Methods: This case-control study was conducted at the Dental OPD of Ziauddin University Hospital and Liaquat National Hospital Karachi Pakistan from January 2020-2021. A total of n=60 participants, 15 each of OSCC with and without periodontitis and 15 controls of periodontitis alone and 15 healthy controls were included in the study. The salivary levels of chemerin were measured by ELISA. The mean salivary chemerin level was compared using Kruskal-Wallis's test among the stages, sites and grades of OSCC. A p-value <0.05 was considered statistically significant. Results: The mean age of study participants was estimated as 43.42±13.19 years (range: 20-60 years). The mean salivary chemerin levels in OSCC were highest in the late stages; 18.88±8.8 ng/ml in stage III and 17.63±5.09 ng/ml in stage IV. A statistically significant difference was observed in mean salivary chemerin levels concerning the stage of OCSS (p=0.025). Furthermore, periodontal status was statistically associated with the site of the tumor (p<0.05). Conclusion: In OSCC and periodontitis, salivary chemerin levels were shown to be higher compared to healthy controls (p=0.025). Therefore, it can be utilized as a new therapeutic target for detecting tumorigenesis. Keywords: Chemerin; Oral Squamous Cell Carcinoma; Periodontitis; Periodontal Disease; Saliva; Salivary Chemerin Level.